Model Strategi Keunggulan E-Brand Love: Studi Kasus E-Commerce di Indonesia - Nadira Hasanah Sahupala; Rainier Hendrik Sitaniapesy (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study aims to develop a new theoretical model to address the research gap and inconsistencies in previous findings and expert opinions regarding the influence of brand trust on purchasing decisions. To bridge this gap, we propose the Brand Love Advantage model, which is conceptually grounded in the Resource Advantage Theory. The study employed purposive sampling with a total of 100 respondents. Data were analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS software. The findings reveal that E-Brand Trust, E-Brand Awareness, and E-FoMo (Fear of Missing Out) each have a significant effect on the E-Brand Love Advantage. Furthermore, E-Brand Love Advantage significantly influences E-Purchase Decision. All four hypotheses proposed in this study are supported by the data. Theoretically, this research contributes to the development of the Resource Advantage Theory by demonstrating the strategic role of emotional brand connections—specifically, brand love—in enhancing digital brand competitiveness and influencing consumer decision-making.